Tinjauan Keadaan Fasilitas Sanitasi Obyek Wisata Pura Tirta Sudamala Kelurahan Bebalang, Kabupaten Bangli Tahun 2017 - Gede Agus Depantara; I Made Bulda Mahayana (Poltekkes Kemenkes Denpasar, 2019)
Abstract Sanitation of public places is a disease prevention effort that focuses its activities on the cleanliness / health of public places (TTU) in serving the public in connection with the activities of the public places physiologically, psychologically, prevent the occurrence of disease or accidental transmission As well as aesthetics, inter-occupants, users, and the surrounding community. This research is a type of descriptive research with direct observation to the location and describes the condition of the location which includes the condition of waste facility, public toilet / toilet and canteen in accordance with the field. In this study used an observation sheet with different items. To know the state of sanitation facilities used two categories of assessment that is eligible and less qualified. The research was conducted in Pura Tirta Sudamala Banjar Sedit Bebalang Village, Bangli Sub-District, Bangli Regency using obervation technique. All items are 46 items. The results of the review of the condition of the sanitation facilities of the temple attractions tirta sudamala kelurahan bebalang, bangli regency eligible to get a score of 31 scores while not to meet the requirements of 15 scores, so the state of sanitary facilities in the temple tirta sudamala in the category qualify because the category of the state Eligible 0-23 and eligible categories 24-46. Keywords : Sanitation, Tourism Object, Public places